Use of a new skin colour measurement method for the investigation of relationship between skin and tooth colour - Burak Yılmaz; Işın Kürkçüoğlu; Ulviye Şebnem Büyükkaplan; Nurullah Türker (Istanbul University, 2020)
Purpose: There is conflicting information about the relationship between tooth color and skin color in the literature. The aim of the present study was evaluation of the correlation between L, a, b values of skin and tooth shade using a new skin color measurement method. Materials and Methods: CIELab values of teeth were obtained through measurements from the middle third of the labial surfaces on central incisors of individuals using a clinical spectrophotometer. CIELab values of the skin were measured through facial images using a software which was manufactured for present study. A statistical analysis program (SAS 9.4) was used for the analysis of the data. Kolmogorov-Smirnow test, t-test, and multivariate regression analysis were used to evaluate the data (α=0.05). Results: Correlations between variables revealed that while the lowest and statistically insignificant correlations were observed with a* values of the skin, significant correlations did not exceed moderate level (p<.05). When considering regression analysis results, b* values of the skin had a statistically significant effect in describing b* values of the tooth, while L* and a* values of the skin were observed to be insufficient in describing L* and a* values of the teeth. Conclusion: Results of this study suggest that different significant correlations were observed between the skin and tooth color for different L*, a*, and b parameters (p<0.05 and p<0.01). The results indicated that skin color can be used for tooth color selection in case of loss of natural teeth or when discoloration is present on existing teeth.